Securities Tokenization: The Third Wave Of Financial Market Evolution -world Bank Bond-i Case Study- - Babas, Mounira (جامعة الوادي - University of Eloued, 2023)
This research aims to study securities tokenization technology as the third wave of financial markets development, with a review of the experience of the World Bank in the field of issuing i-bonds, using the descriptive analytical approach. It was concluded that securities tokenization is an innovative technology in the financial markets based on blockchain technology -whether the tokenization is off-chain or native in it- has many advantages, such as increasing market liquidity, expanding the investor base, automating the life cycle of securities, settlement and delivery of securities, publishing their prices in real time and reducing cost. The World Bank's experience is considered the first and pioneering experience in this field, through the issuance of the first tokenized bond in 2018, which achieved many advantages such as learning, efficiency, transparency and auditing.
مقال
Keywords: : Financial Markets ; Tokenization ; Securities Tokenization ; Bond-i ; World Bank. ; Financial Markets ; Tokenization ; Securities Tokenization ; Bond-i ; World Bank.